ANALISIS PENGARUH PERTUMBUHAN EKONOMI DAN INFLASI TERHADAP TINGKAT KEMISKINAN DI KABUPATEN HULU SUNGAI TENGAH TAHUN 2005-2016 - RAHDA RAHDA; MUHAMMAD Anshar Nur (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
The purpose of this study was to determine the effect of economic growth and inflation on the level of poverty in the Tegah Hulu Sungai Regency. The object of research is limited to the variables of economic growth and inflation as independent variables and the level of poverty as the dependent variable. The results of the study, obtained simultaneously (together) show that economic growth and inflation affect the level of poverty in the Hulu Sungai Tengah district (2005-2016). Partially the inflation variable has a positive influence on the level of poverty in Hulu Sungai Tengah Regency and economic growth does not affect the level of poverty in the Hulu Sungai Tengah Regency. Keywords: economic growth, inflation, poverty level